2010
DOI: 10.1159/000290044
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Exercise Reduces Tumor Necrosis Factor-α Production in Response to Lipopolysaccharide in Mice

Abstract: Objective: Stressful exercise reduces the plasma pro-inflammatory cytokine concentration in response to lipopolysaccharide (LPS). The aim of this study was to clarify the mechanism of exhaustive exercise-induced suppression of the plasma tumor necrosis factor (TNF)-α concentration in response to LPS. Methods: Male C3H/HeN mice (n = 66) were randomized to treadmill running to exhaustion (Ex) or a sedentary (Non-Ex) condition. Monocytes and splenic macrophages were collected from some animals, and other animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…6). This phenomenon, that pathogen-induced increases in plasma TNF-α concentrations are attenuated by prior exhaustive exercise, seems to be similar to that of LPS-induced TNF-α responses in plasma 35,36,60) . Therefore, intense exercise inhibits poly I:C, R-848 and CpG DNAinduced pro-inflammatory cytokine production, which might increase the risk of infection with viruses (Fig.…”
Section: Strenuous Exercise-induced Tnf-α Suppression In Response To supporting
confidence: 51%
See 2 more Smart Citations
“…6). This phenomenon, that pathogen-induced increases in plasma TNF-α concentrations are attenuated by prior exhaustive exercise, seems to be similar to that of LPS-induced TNF-α responses in plasma 35,36,60) . Therefore, intense exercise inhibits poly I:C, R-848 and CpG DNAinduced pro-inflammatory cytokine production, which might increase the risk of infection with viruses (Fig.…”
Section: Strenuous Exercise-induced Tnf-α Suppression In Response To supporting
confidence: 51%
“…Although Colbert et al 59) reported that exercise-induced changes in the plasma cytokine concentrations are not dependent on tissue (liver, lung and muscle) mRNA expression in mice, they did not find any impact of pathogens, such as LPS, on exercise-induced cytokine production. Recently, Tanaka et al 60) reported that the cell-surface expression of TLR4 on macrophages is unchanged by exhaustive exercise (Fig. 4a).…”
Section: Cell Biological Mechanisms Underlying Strenuous Exercise-indmentioning
confidence: 90%
See 1 more Smart Citation
“…One group contained exhaustive exercising mice (EX, n = 12), and the other group contained non-exercising mice (N-EX, n = 11). The EX mice were run on a treadmill to exhaustion, and N-EX mice were kept at rest [4,7]. Mean time to exhaustion for EX mice was 65 ± 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, we and other researchers have found that high concentrations of proinflammatory cytokines, for example tumor necrosis factor (TNF)-a, in plasma were strongly inhibited by exhaustive exercise before challenge of rodents with lipopolysaccharide (LPS), a gram-negative bacteria component [2][3][4]. In addition, it has been reported that exercise stress might be associated with increased susceptibility to viral infections [5,6].…”
Section: Introductionmentioning
confidence: 98%